Needs analysis on learning material development of English specific purpose in teacher education elementary school program at Muhammadiyah University Palangkaraya - Elhawwa, Tazkiyatunnafs (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
The aim of this investigation was to outline a need analysis for creating ESP teaching materials for students enrolled in the PGSD study program at Muhammadiyah University of Palangka Raya. This study concentrated on 40 subjects' demands for ESP material from their points of view. The result revealed that: (1) students (35%) joined ESP courses out of necessity to improve their English literacy and have a good job; (2) subjects (40%) believed they studied ESP to understand English text; (3) subjects (35%) experienced difficulty understanding the meaning of the text; and (4) subjects (50%) had trouble reading English text. (4) The findings suggested that (a) the half of learners (50%) would like to demonstration as their favorite classroom activities; (b) Browsing Internet (50%) as favorite activities to improve language skills (c) English movie was preferred dominantly (65%) as the media to perform language exposure; (d) Internet was liked best (65%) as source material; (e) 100 minute was preferred mostly (75%) as the suitable time for ESP learning; (f) product assessment was liked best (35%) as the appropriate model of assessment; and (g) the coverage topics liked best (40%) was texts related to the field of study.